2020
DOI: 10.1016/j.envpol.2020.115630
|View full text |Cite
|
Sign up to set email alerts
|

The short- and long-term associations of particulate matter with inflammation and blood coagulation markers: A meta-analysis

Abstract: Inflammation and the coagulation cascade are considered to be the potential mechanisms of ambient particulate matter (PM) exposure-induced adverse cardiovascular events. Tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), interleukin-8 (IL-8), and fibrinogen are arguably the four most commonly assayed markers to reflect the relationships of PM with inflammation and blood coagulation. This review summarized and quantitatively analyzed the existing studies reporting short- and long-term associations of PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 103 publications
1
27
0
Order By: Relevance
“…Second, PM 2.5 induction of a local or systematic inflammatory reaction is the major pathologic basis for the onset and progression of several related diseases [ 38 ]. Evidence from a meta-analysis [ 39 ] also showed that PM exposure increased the levels of fibrinogen and TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Second, PM 2.5 induction of a local or systematic inflammatory reaction is the major pathologic basis for the onset and progression of several related diseases [ 38 ]. Evidence from a meta-analysis [ 39 ] also showed that PM exposure increased the levels of fibrinogen and TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…Fine particles (PM 2.5 , with a diameter smaller than 2.5 μm) and ultrafine particles (UFP, with a diameter smaller than 0.1 μm) can reach the alveoli deep inside the lungs, and even penetrate through the epithelia into the bloodstream [ 23 , 27 , 28 ]. The inhaled pollutants cause epithelium injuries and activate the immune system to launch a cascading inflammation response [ 22 , 23 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to excessive concentrations of air pollutants has been implicated in the etiology and/or worsening of several pathological conditions, ranging from cardiovascular and neurological diseases to cancer [1][2][3]. It is now generally recognized that one of the main pathological mechanisms elicited by airborne pollutants, including particulate matter (PM), is based on the activation of a systemic inflammatory cascade [4,5]. After inhalation, fine PM deposits throughout the respiratory tract and damages the airway epithelium.…”
Section: Introductionmentioning
confidence: 99%